PERAN KETELADANAN KYAI DALAM MEMBENTUK SIKAP TAWADHU’ SANTRI - Zahrotunnahdliyah, Hilmah; Ilahiyah, Iva Inayatul; Muslih, Imam (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract: This research is intended to answer the questions: 1. What is the exemplary role of the Kyai at the Darul Falah 5 Cukir Jombang Islamic Boarding School 2. What is the role of the Kyai in forming the tawadhu' attitude of students at the Darul Falah 5 Cukir Jombang Islamic Boarding School 3. What are the supporting and inhibiting factors for the Kyai's role in forming the tawadlu' attitude of students at the Darul Falah 5 Cukir Jombang Islamic Boarding School. This research is qualitative field research which is descriptive qualitative in nature. Data collection techniques in this research used observation, interviews, documentation and triangulation techniques. Then analyzed using qualitative descriptive analysis. The results of this research show that the role of the kyai at the Darul Falah 5 Islamic Boarding School has a big influence on the attitudes, personality and spirit of the students. There are also many kyai attitudes that can be emulated by the students, including always being kind to others, always respecting everyone around them, being humble, never showing their strengths to others and other things that should be exemplary for the students and applied in everyday life. This is one of the best ways to instill an attitude of tawadhu' for students. Not only that, by teaching the importance of implementing good manners such as respecting elders and respecting younger ones in order to maintain harmony both with kyai and students in Islamic boarding schools and parents at home. In the Darul Falah Islamic Boarding School, the 5 most important things that need to be considered so that students have an attitude of tawadhu' are istiqomahan in carrying out sunnah and obligatory worship. Because if the students are used to worship, the attitude of tawadhu' can easily be formed in every student at the Islamic Boarding School.